Ocular Kaposi Sarcoma as the Initial Manifestation of Human Immunodeficiency Virus (HIV) Infection: A Case Report: Doi: 10.36351/pjo.v41i2.1978 - Mahyuddin, Mutmainah; Anggraini, Neni; Nugroho, Agung; Susanto, Eka (Pakistan Journal of Ophthalmology, 2025)
Kaposi sarcoma associated with Human Herpesvirus-8 (HHV8) infection, is a low-grade malignant vascular spindle-cell tumour, commonly linked to acquired immunodeficiency syndrome (AIDS). This case report highlights a rare presentation of ocular KS leading to diagnosis of Human Immunodeficiency Virus (HIV) infection. A 25-year-old otherwise healthy Indonesian male presented with slow-growing erythematous masses on the superior eyelid and conjunctiva, two months after colliding with a door. Excisional biopsy confirmed KS, and subsequent HIVtest was positive. A multidisciplinary approach was initiated to evaluate and treat the underlying AIDS and KS. Recognizing ocular KS as an initial sign of HIV through thorough examination is crucial for accurate diagnosis, prompt treatment, and improved prognosis.